ANALISIS DATA KUNJUNGAN WISATAWAN MANCANEGARA KE BALI DENGAN DATA MINING - Sasrawan, I Putu Hedi; Budiningsih, Ni Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 12 (2022): Vol.11.12. DESEMBER 2022[4234-4463], 2022)
The tourism industry is the main industry in the Balinese economy. Therefore, tourist visits data is interesting to analyze. The data to be analyzed are data on the level of foreign tourist arrivals, GDP per capita, exchange rates against the Rupiah, and the total population of the Australia, the United States, Japan, Malaysia and France. The time range used is 2014 to 2020. The data mining method can be used to objectively find patterns from the data. Orange Data Mining software is used in this study because it is based on a GUI that makes it easy for users. The methods used are decision trees, linear regression, and K-Means. The results show that a country with a larger GDP per capita has a higher influence on increasing tourism visits to Bali.